New Russian antiarrhythmic agent nibentan: clinical effectiveness and pharmacokinetics in supraventricular arrhythmia management - A. E. Radzevich; V. G. Valiev; V. A. Gorshkov; E. M. Zeltyn; A. B. Bezprozvanny; E. N. Ostroumov; S. A. Appolonova (Российский кардиологический журнал)
Clinical effectiveness of a new Russian antiarrhythmic agent nibentan, Class III, was studied in various supraventricular arrhythmias. In total, 220 patients with atrial fibrillation (AF), atrial flutter (AFl), supraventricular tachycardia (SVT) and frequent supraventricular extrasystoles (SVE) were examined. ECG monitoring and echocardiography data, electrolyte balance and blood biochemistry were assessed. left ventricular myocardial kinetics and perfusion were studied by computed Tc-99 scintigraphy (Siemens-E. CAM camera, two detectors, 90 degree rotation, 16 gates per cardiac cycle; data analysis with 4DM sped program). Nibentan pharmacokinetics and pharmacodynamics, as well as its metabolite levels, were measured with highly effective chromatography-mass spectrometry. Nibentan was highly effective in various supraventricular arrhythmias, without affecting central hemodynamics or left ventricular perfusion. There was a positive correlation between nibentan administration time, its active metabolite detection, plasma Mg level increase, and QTinterval elongation. Conclusion: Nibentan, a new antiarrhythmic agent, is highly effective for supraventricular paroxysmal arrhythmias (AF, AFl, SVT) management. Due to long QT and ventricular tachycardia risk, nibentan should be administered at cardiac resuscitation departments or intensive care units only.